IgE in childhood asthma: relevance of demographic characteristics and polysensitisation. Issue 12 (23rd July 2010) - Silvestri, M; Pistorio, A; Battistini, E; Rossi, G A
Abstract : Background: Despite the therapeutic efficacy of the anti-IgE monoclonal antibody, the role of IgE in allergic asthma is still a matter of debate. This may be mostly relevant in childhood, where a wide range of total serum (s) IgE levels is often detected. Aim: To evaluate whether the relationships between total or allergen-specific sIgE levels and the clinical markers of allergic inflammation and the pulmonary function values might be affected by the demographic characteristics of the patients or by the presence of multiple sensitisations to allergens. Methods: 64 asthmatic children sensitised to house dust mites (HDM) were evaluated. The role of age, sex and multiple sensitisations was evaluated by multiple regression model (MRM) analysis. Results: Total and HDM-specific sIgE levels (Log) showed similar moderate-to-strong correlations with exhaled nitric oxide (FENO) and blood eosinophilia (Log) (p<0.0001) but not with forced vital capacity, forced expiratory volume in 1 s (FEV1 ), %FEV1 change after salbutamol. The positive associations between total sIgE levels and Log FENO levels or Log blood eosinophilia were also detected by MRM analysis. Age brought a negative, although limited, contribution to FENO levels and blood eosinophilia (p<0.043). Positive similar associations were also detected between HDM-specific sIgE levels and FENO levels or blood eosinophilia; however, no significant contribution of age or of other covariates was detected. Conclusion: In childhood allergic asthma, total and HDM-specific sIgE levels are tightly linked to markers of allergic inflammation but not to pulmonary functions. These relationships are weakly affected by age but not by sex or by the presence of multiple sensitisations.